PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN POWER POINT TERHADAP MOTIVASI BELAJAR SISWA SD KELAS IV PADA PEMBELAJARAN IPAS - Kiki Ramzi; Erma Yulaini; Henni Riyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Power point media is an interesting media to foster enthusiasm, interest, motivation and activate students in the teaching and learning process in the classroom. Learning motivation is a strength or encouragement by teachers to students so that students become more active and able to increase student involvement in the learning process. This study aims to determine the effect of the use of power point learning media on the learning motivation of fourth grade elementary school students in science learning. The research method uses quantitative research. The population of this study was fourth grade students at SD Negeri 5 Tulung Selapan as many as 22 students in the control class and 22 students in the experimental class. Data collection techniques used documentation and questionnaires. The results of the study showed that the use of power point learning media had an effect on the learning motivation of fifth grade elementary school students in science learning. This can be seen based on the t-test that has been carried out with the acquisition of a sig value = 0.000 <0.05 so that it can be stated that H0 is rejected and Ha is accepted.